Roles of Siblings in Folktales - Pecková, Kateřina (Univerzita Pardubice, 2024)
This master thesis deals with the portrayal of siblings and sibling relationships in folktales from four collections. The theoretical part introduces the narrative form of folktales, presents an overview of the changing reception of folktales, and discusses the structuralist approach, one of the most significant approaches for analysing tales. The main part of this paper is strongly inspired by the study of sibling relationships in young children's literature conducted by Kramer, Noorman and Brockman in 1999. By replicating their methodology, this paper attempts to analyse folktales in terms of the birth order of main characters, their gender, and themes, aiming to discover general characteristics of siblings in folktales and compare the results with the findings from the original research.
Role sourozenců v pohádkách a lidových vyprávěních
Keywords: lidové pohádky; druh postavy; sourozenci; pořadí narození; strukturalismus; folktales; character type; siblings; birth order; structuralism